Systematic Literature Review: The Use of English Song on Spotify Application in Learning English - Fitri, Alda Nuzul; Zoelvi, Naila Izzati; Hadriana, Hadriana (SCOPE: Journal of English Language Teaching, 2024)
In learning, teachers sometimes use media to support students' learning so they can better enjoy and understand what is being said. This research aimed to identify the use of English songs on the Spotify application in English language learning. This study used a systematic literature review and selected 15 articles from the exclusion and inclusion process. The research result is using the Spotify application can improve students' speaking and listening skills. Furthermore, most students also have a good perception of using the Spotify application in learning English. They also recommend using the Spotify application as a learning medium that makes them en.oy and interesting. Apart from improving students' speaking and listening, using the Spotify application can also increase students' vocabulary which they get from the lyrics of the songs on the Spotify application.